Ekstrakurikuler “Tari Topeng Ireng” sebagai Strategi Penanaman Percaya Diri Siswa MIS Al Islam Tempel Sleman Yogyakarta - Noor Masruroh; Ahmad Shofiyuddin Ichsan; Muhammad Asrofi (AL-FURQAN, 2020)
This research aims to the dance extracurricular "Tari Topeng Ireng" as a strategy to increase student confidence in MIS Al Islam Tempel Sleman Yogyakarta. This research is qualitative research with a phenomenological approach. Retrieval of data in this research using observation, interviews, and documentation, while analyzing the data, researchers used the Miles and Huberman Interactive Analysis models. The results obtained in this research are the coach uses five methods, including lecture method, peer tutor method, demonstration method, exploration method, and discussion method. Through these methods, making students confident in appearing publicly with various characters. The supporting factors of the implementation of this extracurricular are 1). High student interest, 2). Professional builder quality, and 3). Facilities and infrastructure in practice are sufficient. While the inhibiting factors, among others: 1). Motoric students who are still lacking, 2). Schedule of activities that collide with other activities, and 3). School transportation that does not yet exist.